2022
DOI: 10.1038/s41598-022-12134-3
|View full text |Cite|
|
Sign up to set email alerts
|

ZnO size and shape effect on antibacterial activity and cytotoxicity profile

Abstract: The aim of our work was the synthesis of ZnO nano- and microparticles and to study the effect of shapes and sizes on cytotoxicity towards normal and cancer cells and antibacterial activity toward two kinds of bacteria. We fabricated ZnO nano- and microparticles through facile chemical and physical routes. The crystal structure, morphology, textural properties, and photoluminescent properties were characterized by powder X-ray diffraction, electron microscopies, nitrogen adsorption/desorption measurements, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(90 citation statements)
references
References 63 publications
4
85
0
1
Order By: Relevance
“…Whereas the order of antibacterial activity against S. aureus was as follows: Ag 3 PO 4 (MIC/MBC: 2/4 mg/mL) > Ag-Ag 3 PO 4 (MIC/MBC: 2/8 mg/mL) > Ta-Ag 3 PO 4 (MIC/MBC: 4/8 mg/mL) > Se-Ag 3 PO 4 (MIC/MBC: 4/8 mg/mL), respectively ( Table 2 and Figure 4 ) . Small nanoparticle size possibly internalized bacterial cells, through ion diffusion and free radicals generation, which further enter the cells, destroying cellular components such as proteins, DNA, and lipids, as suggested by previous reports [ 48 , 49 ] that the antimicrobial activity increased due to a decrease in the particle size of nanoparticles. According to the findings of the MIC and MBC tests, it was found that Gram-negative bacteria, E. coli , were more susceptible to the tested nanoparticles than Gram-positive bacteria ( S. aureus ).…”
Section: Resultsmentioning
confidence: 81%
“…Whereas the order of antibacterial activity against S. aureus was as follows: Ag 3 PO 4 (MIC/MBC: 2/4 mg/mL) > Ag-Ag 3 PO 4 (MIC/MBC: 2/8 mg/mL) > Ta-Ag 3 PO 4 (MIC/MBC: 4/8 mg/mL) > Se-Ag 3 PO 4 (MIC/MBC: 4/8 mg/mL), respectively ( Table 2 and Figure 4 ) . Small nanoparticle size possibly internalized bacterial cells, through ion diffusion and free radicals generation, which further enter the cells, destroying cellular components such as proteins, DNA, and lipids, as suggested by previous reports [ 48 , 49 ] that the antimicrobial activity increased due to a decrease in the particle size of nanoparticles. According to the findings of the MIC and MBC tests, it was found that Gram-negative bacteria, E. coli , were more susceptible to the tested nanoparticles than Gram-positive bacteria ( S. aureus ).…”
Section: Resultsmentioning
confidence: 81%
“…As such, the aqueous stability of our RB when loaded with ZnO along with the higher DC are not believed to be limiting factors in the antimicrobial response of the new material. From the literature it is known that the smallest-sized and specifically-shaped ZnO NPs [ 41 , 65 , 66 ], higher light energy [ 67 , 68 , 69 ], and certain biofilm properties such as age [ 70 , 71 ] are more likely to reveal the antimicrobial properties, though the extent of the impact for such factors is likely dependent on the type of photosensitizer (PS). For example, a longer biofilm growth period allows for the formation of a mature biofilm that creates a cariogenic environment with low pH (pH < 5.5) [ 72 ], and due to this lower pH, higher ZnO dissociation would occur [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is an inverse relationship between the size of NPs and their activity, i.e., the activity was increased as the size decreased [8]. For example, the nanorod-ZnO exhibited a strong antibacterial activity against E. coli and S. aureus as compared to the microparticles; authors attributed this result to the high surface area [56] due to the small size of the phycosynthesized ZnO-NPs.…”
Section: Antibacterial Activitymentioning
confidence: 99%